Fine Atmospheric Particles from Agricultural Practices in Flanders: From Emissions to Health Effects and Limit Values. (March 2014) - Buekers, Jurgen; Deutsch, Felix; Veldeman, Nele; Janssen, Stijn; Panis, Luc Int
Agriculture can influence air quality via emissions of ammonia, soil dust and soot. These can be emitted into the atmosphere during farming practices, and contribute in different amounts to the total emissions and concentrations of air particulate matter (PM). The exact contribution of Flemish agricultural emissions to total air PM concentrations and to negative health effects are not well known. In this paper, agricultural emissions in Flanders and the processes leading to secondary PM are reviewed, together with their associated health effects. Agricultural ammonia emissions are a major contributor to local formation of secondary PM, and can increase above normal levels during some smog episodes. From a health perspective, secondary PM formed by ammonia is considered less important. Epidemiological studies suggest that combustion-related particles are the cause of negative health effects, although a reduction in ammonia emissions would reduce acidification and eutrophication of ecosystems. The World Health Organization currently considers PM2.5 as the best indicator for assessing human health effects. Setting an additional limit value for combustion-related particles would target potentially more harmful particles.